Voluntary gold certification programs: A viable mechanism for improving artisanal and small-scale mining in Peru?. (August 2022) - Martinez, Gerardo; Smith, Nicole M.; Veiga, Marcello M.
Abstract: Globally, artisanal and small-scale gold mining (ASGM) provides a livelihood for approximately 20 million people directly and millions more indirectly. Despite its economic contributions and job creation for rural communities, the sector continues to be overlooked in local, regional, and national sustainable development plans. Voluntary gold certification programs, created and administered by international NGOs, have emerged as one response to tackle the social and environmental issues associated with the ASGM sector. Although voluntary gold certifications are gaining more traction, their impacts remain unclear. Focusing on Peru, the country with the greatest number of certified artisanal and small-scale gold mining organizations (ASMOs), this paper examines the practical impacts when certification is achieved and identifies the shortcomings. Based on interviews with gold certification staff members and members of certified ASMOs, as well as site visits to certified mining operations, we demonstrate that gold certification programs are driving ASMOs to implement better environmental management and health and safety practices. Certified ASMOs are also benefitting from the economic incentives of selling gold internationally, and they are investing the premiums they receive from certifications into projects that benefit their workers and the mining town. Still, the reach of certification programs remains limited, with only a fraction of miners working for certified ASMOs. This article concludes that although gold certification programs have the potential to improve environmental protection and contribute to rural development, there are challenges that will have to be overcome for small-scale mining organizations to achieve and maintain certification status. Highlights: Voluntary gold certification programs mainly focus on mercury use and rural development. Gold certification programs drive some improvements in artisanal and small-scale mining. Some environmental and development aspects have received less attention. The longer-term viability of certification programs is questioned.